An Enhanced Three Layer Cryptographic Algorithm for Cloud Information Security - Anjana (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The rapid adoption of cloud computing has ushered in unparalleled opportunities for efficient data storage and processing, but it also brings forth significant challenges related to information security. This study focuses on the design and analysis of effective techniques for enhancing information security in cloud computing environments, with a particular emphasis on the hybrid encryption technique. This research delves into the theoretical underpinnings of AES+ChaCha20 and SHA-3 evaluates its suitability for cloud-based applications, considering factors such as encryption strength, computational efficiency, and resistance to cryptographic attacks. The SHA-3 algorithm is employed to generate fixed-size hash values from input data. In this study, the plain text file is encrypted using the AES+ChaCha20, the cipher text file is hashed using the SHA3 algorithm to produce a message digest. Through a comprehensive analysis, including performance benchmarks and security assessments, this study aims to provide a nuanced understanding of the effectiveness of AES+ChaCha20 in mitigating common threats in cloud computing environments. The outcomes of this research contribute valuable insights to the on-going discourse on information security in cloud computing, offering a foundation for the development and implementation of robust security measures. As organizations increasingly rely on cloud services, the findings of this study are poised to inform best practices for securing data and ensuring the confidentiality and integrity of information in cloud-based systems.